Comprehensive analysis of intra-arterial treatment for acute ischemic stroke due to cervical artery dissection. (10th June 2016) - Jensen, Judd; Salottolo, Kristin; Frei, Donald; Loy, David; McCarthy, Kathryn; Wagner, Jeffrey; Whaley, Michelle; Bellon, Richard; Bar-Or, David
Abstract : Objective: The safety and efficacy of intra-arterial treatment (IAT) in patients with acute ischemic stroke (AIS) due to cervical artery dissection (CeAD) has not been formally studied. The purpose of this study was twofold: first, describe a large series with CeAD treated with IAT; second, analyze outcomes with CeAD receiving IAT versus (a) CeAD not treated with IAT, (b) CeAD receiving intravenous thrombolysis (IVT) alone, and (c) non-CeAD mechanism of AIS receiving IAT. Design: Demographics, clinical characteristics, treatment, and outcomes were summarized for all CeAD patients treated with IAT from January 2010 to May 2015. Outcomes included favorable 90 day modified Rankin Scale (mRS) score of 0–2, symptomatic intracerebral hemorrhage (sICH), recanalization (Thrombolysis in Cerebral Infarction 2b-3), procedural complications, and mortality. Outcomes were analyzed with χ 2 tests and multivariate logistic regression. Results: There were 161 patients with CeAD: 24 were treated with IAT and comprised our target population. Dissections were more common in the internal carotid (n=18) than in the vertebral arteries (n=6). All but one patient had intracranial embolus. IAT techniques included thrombectomy (n=19), IA thrombolysis (n=17), stent (n=14), and angioplasty (n=7). Outcomes included favorable 90 day mRS score of 0–2 in 63%, 4 deaths, 1 sICH, and 3 procedural complications. After adjustment, favorable mRS in our target population was similar to comparison populations: (a) in CeAD, IAT versus no IAT (OR 0.62, p=0.56); (b) In CeAD, IAT versus IVT alone (OR 1.32, p=0.79); and (c) IAT in CeAD versus non-CeAD mechanism of AIS (OR 0.58, p=0.34). Conclusions: IAT is a valid alternative therapeutic option for AIS caused by CeAD due to the low complication rate and excellent outcomes observed in this study.